Mosby's physical examination DVD series [ DVD 11, Famale genitalia and rectum - Ball, Jane; Dains, Joyce E.; Seidel, Henry M. (Mosby's physical examination DVD series, 2006)
"This 14 minute video shows the steps needed to examine the female genitalia and rectum, including the proper use of equipment. With the patient in the lithotomy position, it demonstrates how to inspect and palpate the patient's external genitalia, inspect her internal genitalia via a speculum, and perform a bimanual examination and rectovaginal examination of internal structures. The video shows expected findings and highlights selected variations in techniques and expectations for pediatric and geriatric patients. In addition, it uses graphics to reveal what is happening internally during the examination."--Publisher's website